Dare to Dream : ...... then do it ; what successful people know and do - Maxwell, John C. (Nashville : Countryman, 2006)
Biography of Indian hotelier, Mohan Singh Oberoi, b. 1900.
Includes bibliographical references.
Keywords: Personal development